PENGELOLAAN AKREDITASI SEKOLAH (STUDI SITUS SD NEGERI 2 MRANTI KECAMATAN PURWOREJO KABUPATEN PURWOREJO) - Supriyatno Supriyatno; Eko Supriyanto; Maryadi Maryadi (Universitas Muhammadiyah Surakarta, 2013)
The onjectives of this research are to describe (1) the preparation of school self-evaluation in improving school accreditation; (2) The visitation in improving school accreditation; (3) The results of school accreditation. The type of the research is qualitative and uses ethnography design. The site of the study is SD Negeri 2 Mranti Purworejo District, Purworejo. Techniques for collecting data used are interviews, observations, and documentation. The results of this research are as follows: (1) Preparation of school self-evaluation is conducted by a special team formed by the principal. The preparation done before the new school year, it takes place by collecting data from the SNP. EDS is consisting of EDS instrument and the physical evidence for each item SNP. The preparation is conducted byhaving a checklist for each item in the SNPs form that describes the real condition of the school; (2) the visitation process in improving schools accreditation runs smoothly and according to the procedure. The process begins with the submission of the letter that comes with the implementation of the accreditation document to School Accreditation Association (BAS) of district; (3) the accreditation result increases from 79 in 2005 to 86.81 in 2010.